Comparison of Service Quality Between Purchasing Airline Tickets Through the Traveloka Application and Ticket.com In Yogyakarta - Alya Berliani Ilhaeda; Nerys Lourensius L Tarigan (Jurnal Ekonomika dan Manajemen, 2026)
This research is driven by the rapid evolution of information technology in Indonesia, which has fundamentally reshaped consumer behavior toward utilizing Online Travel Agent services for booking airline tickets. The primary objective of this study is to analyze and compare the service quality between two prominent platforms, Traveloka and Tiket.com, specifically among users located in the Yogyakarta region. The evaluation is framed around five core dimensions of service quality, which include tangibles, reliability, responsiveness, assurance, and empathy. Adopting a comparative quantitative approach, primary data was gathered from respondents selected through a targeted sampling technique. Prior to the main analysis, all research instruments underwent rigorous testing to ensure they met the necessary standards for validity and reliability. The statistical analysis revealed significant disparities across all service quality dimensions between the two applications. These findings suggest that each platform possesses unique service characteristics in the eyes of consumers, particularly concerning their visual interfaces, system stability, and customer support efficiency. Consequently, both companies are encouraged to further refine their service responsiveness and technical dependability to better satisfy diverse user expectations. While this study offers valuable insights into digital service quality, it is constrained by its specific geographic focus and product category. Future researchers are advised to expand the geographical scope and incorporate additional variables, such as customer loyalty or price perception, to achieve a more comprehensive understanding of the industry.